SISTEM MANAJEMEN PERSEDIAAN BARANG PADA RETAILER MENGGUNAKAN METODE SINGLE EXPONENTIAL SMOOTHING - Husni Angriani (STMIK KHARISMA Makassar, 2017)
Determining the amount of stock for the right inventory becomes an issue in meeting the number of consumer needs for retailers. The problem affects the process of selling goods for retailers to be hampered. This research is developed a model of determining the amount of inventory on a retailer by using a single exponential smoothing method to forecast quantity order or how many items should be in the message to meet the end consumer demand.The results of this research indicate that the system developed can make the determination of the amount of goods to be ordered by retailers in meeting customer needs. Testing this system using sales data conducted during a month that is implemented into the system. The result of data entered into the system is shown that the retailer's inventory cost is too large. This is because too much inventory on each side is not in accordance with consumer demand, so it can cause harm to all parties. The developed system can determine the exact amount of goods ordering on retailers with single exponential smoothing method.